Sediment metal enrichment and ecological risk assessment of ten ports and estuaries in the World Harbours Project. (June 2020) - Birch, G.F.; Lee, J.-H.; Tanner, E.; Fortune, J.; Munksgaard, N.; Whitehead, J.; Coughanowr, C.; Agius, J.; Chrispijn, J.; Taylor, U.; Wells, F.; Bellas, J.; et al.
Abstract: Ten global harbours were assessed for sediment quality by quantifying the magnitude of anthropogenic change and ecological risk. Anthropogenic change (enrichment) was high for Derwent River and Sydney estuary, moderate for Santander Harbour, Rio de Janeiro and Dublin Port, slight for Hong Kong, minimal for Darwin. All 10 enrichment indices used showed similar results. Derwent River sediment was rated at high ecological risk, followed by Sydney and Santander estuaries with moderate risk. Auckland and Darwin sediments exhibited minimal ecological risk and sediment in the remaining harbours (Dublin, Hong Kong, Ravenna, Ria de Vigo and Rio de Janeiro) were assessed at slight ecological risk. The extraordinary variety of environments and types/quantities/qualities of data investigated resulted in as much a critique and development of methodology, as an assessment of human impact, including unique techniques for elemental normalisation and contaminant classification. Recommendations for an improved technical framework for sediment quality assessment are provided. Graphical abstract: Unlabelled Image Highlights: Ten global harbours were assessed for anthropogenic change (AC) and ecological risk (ER) AC was high for Derwent River, Santander and Sydney estuaries AC was moderate for Rio de Janeiro and Dublin Port, slight for Hong Kong, minimal for Darwin. Derwent River sediment was rated at high ER, Sydney and Santander estuaries with moderate risk. An improved technical framework for sediment quality assessment is provided.